2003
DOI: 10.1080/14034940310005349
|View full text |Cite
|
Sign up to set email alerts
|

Comparative intervention study among Danish daycare children: the effect on illness of time spent outdoors

Abstract: Our negative findings are in accordance with the theory that illness among daycare children is largely a result of contact among children and the hygiene standards of the institution, and thus these are the factors that may need to be addressed to reduce the level of illness among daycare children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 5 publications
5
13
2
Order By: Relevance
“…The overall illness incidence was 1.55 illness episodes per 100 child-days and was not statistically significantly different for children at nature and conventional preschools. The incidence of illness we found is consistent with prior study findings reporting the incidence of illness episodes in conventional preschools [22,42]. Respiratory illnesses were the most common type of illness, which is also consistent with current literature on preschool illnesses [22,[42][43][44].The overall percentage of days of absence due to illness of 2.2% was found to be similar to a study of illnesses in conventional preschools conducted in Seattle, Washington but lower than prior studies conducted in New York and abroad which showed absence from preschool due to illness ranging from 4.1% to 10.9% [22][23][24]45].…”
Section: Illnesssupporting
confidence: 92%
See 1 more Smart Citation
“…The overall illness incidence was 1.55 illness episodes per 100 child-days and was not statistically significantly different for children at nature and conventional preschools. The incidence of illness we found is consistent with prior study findings reporting the incidence of illness episodes in conventional preschools [22,42]. Respiratory illnesses were the most common type of illness, which is also consistent with current literature on preschool illnesses [22,[42][43][44].The overall percentage of days of absence due to illness of 2.2% was found to be similar to a study of illnesses in conventional preschools conducted in Seattle, Washington but lower than prior studies conducted in New York and abroad which showed absence from preschool due to illness ranging from 4.1% to 10.9% [22][23][24]45].…”
Section: Illnesssupporting
confidence: 92%
“…Two studies, one conducted in Denmark and one in Sweden, evaluated the effects of outdoor time at preschool on the incidence of illness and reported mixed results. The Danish study found no association between outdoor time and risk of illness, and the Swedish study found that exposure to outdoor time was associated with decreased illness incidence [22,23]. A study conducted in Norway compared illnesses between children at outdoor and conventional preschools; however, preschools were classified as outdoor if they spent a minimum of 3.5 hours outside per day.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of infections may be slower and doses of microbes lower due to the expanded outdoor space compared to the indoors, as found in studies of measles epidemics in Guinea Bissau . Outdoor stay at DCCs has been shown both to reduce and not to reduce absence due to illness . However, being outdoors has other beneficial observed effects on children′s health, such as being more physically active .…”
Section: Introductionmentioning
confidence: 99%
“…Danish authors did not find the connection between the amount of time children spend outdoors and in the kindergarten. However, they did find that the higher level of hygiene standards has an effect on reducing the incidence of respiratory tract infections [6]. This study shows that about 30% fewer sick days are present with children under parental care, who do not attend classic kindergartens.…”
Section: Discussionmentioning
confidence: 68%
“…By changing the norm (by increasing the size of the space in which children stay and creating age-mixed groups), the rate of respiratory infections could be reduced. In Denmark, children enter the national kindergartens at the age of 18 months [6]. In the age group of 18-24 months, there are six children in the group, who are looked after by two people, while children 24-36 months are in groups of 12 with two educators assigned.…”
Section: Discussionmentioning
confidence: 99%